Rekonstruksi Pengawasan Hukum Administrasi terhadap Kendaraan Over Dimension and Over Loading (ODOL) di Provinsi Kalimantan Timur - Yeni Santi; Agus Prasetyo; Tubagus Angling Perdana (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The supervision of Over Dimension and Over Loading (ODOL) vehicles in East Kalimantan Province still faces complex challenges involving institutional, technical, and socio-cultural aspects. This study aims to evaluate the effectiveness of administrative law supervision of ODOL vehicles carried out by the East Kalimantan Provincial Transportation Agency and to identify the obstacles encountered in implementing legal enforcement in the field. This research applies a juridical-normative and empirical approach with a descriptive-qualitative method. Data were collected through in-depth interviews with 41 supervisory officers, field observations at two active weighbridge locations (Km 38 Balikpapan and Km 14 Samarinda), and documentation analysis from the Transportation Agency, Land Transportation Management Center, and the Ministry of Transportation. The findings indicate that supervision has been conducted through joint operations among institutions, weighbridge monitoring, and outreach to logistics companies. However, its effectiveness remains low, with administrative sanctions imposed on only 23% of the violations recorded in 2023. Major obstacles include limited supervisory personnel, non-integrated digital infrastructure, and low legal awareness among logistics operators and drivers. This study concludes that the effectiveness of ODOL supervision depends on the synergy between institutional capacity, technological integration, and community legal culture. It recommends developing a simple digital supervision system integrated with vehicle inspection (KIR) data and enhancing public participation to establish a transparent and sustainable monitoring mechanism. These efforts are expected to support the achievement of the national Zero ODOL 2026 target in East Kalimantan.